Larval morphology and diagnosis of the Giant Microcaddisfly species, Ugandatrichia spp. (Hydroptilidae: Trichoptera) in Thailand - Laudee, Pongsak (Zootaxa, 2008)
Fifth instar larval morphology and ultrastructure of Ugandatrichia kerdmaung Malicky and Chantaramongkol 1991, U. maliwan Malicky and Chantaramongkol 1991, U. honga Olah 1989 and U. hairanga Olah 1989 were investigated. The Ugandatrichia spp. are case bearing and net spinning caddisflies. The presence, number and characteristics of the sclerites on abdominal sterna III, IV, and V can be used to identify the Ugandatrichia species found in Thailand. The larva of U. honga has no sclerites on the abdominal sterna; that of U. hairanga has a sclerite on each of abdominal sterna III, IV, and V; that of U. kerdmuang has a sclerite on each of abdominal sterna IV and V, and that of U. maliwan has six sclerites on abdominal sterna IV and V. SEM micrographs of Ugandatrichia spp. showed that the spherical palpiger has a labial palp, an anterior silk gland opening, and dense bristles anteriorly and inside of its mouth. There are three main types of integument surface: an irregular dome shape which is found on the head, pronotum, mesonotum, and metanotum; a regular dome shape which is found on the membrane between the nota; and an amoeboid, dot shape which is found on the abdominal segments.